Reproductive factors and risk of spontaneous abortion - Noordiati Noordiati; Seri Wahyuni; Greiny Arisani; Wahidah Sukriani (Jurnal Kesehatan Ibu dan Anak, 2020)
One of the causes of bleeding and infection in pregnant women is abortion-a failure reproduction. Spontaneous abortion is a pregnancy complication that can affect women both physically and psychologically. This research was purposed to find out the spontaneous abortion incidence, the relation of mother’s age to the spontaneous abortion incidence by controlling the others risk factors such as the interval of the pregnancy, parity, and the usage of contraception. Type to the research is a case-control study where the number of subjects is 174 of pregnant women who have a spontaneous abortion as the case and who have no spontaneous abortion as the controlled group. The univariable used distribution of frequency, the analysis of bivariable used chi-square test, and the analysis of multivariable used multiple logistic regression analysis. The proportion of case group was The largest sample proportion in the case group for the age variable was at the age of 20-35 years (48.3%), pregnancy interval ?2 years (56.9%), parity gave birth more than 4 times (62.1%), and use contraception (56.9%). Meanwhile, the control group for the variable age was at the age of 20-35 years (78.4%), pregnancy interval ?2 years (79.3%), parity between 2-3 births (57.8%), and use contraception (73.6%). All variables were associated with the incidence of spontaneous abortion as follow age of mother <20 years old (p-value 0.000; OR 4.06; 95% CI 1.72-9.57), age of mother >35 years old (p-value 0.000; OR 3.61; 95% CI 1.17-11.07), pregnancy interval (p-value 0.002; OR 2.90; 95% CI 1.38-6.10), parity (p-value 0.013; OR 2.24; 95% CI 1.12-4.51), use of contraception (p-value 0.000; OR 3.43; 95% CI 1.59-7.34). The most dominant factor was mother age <20 years old (OR: 3.82; 95% CI 1.64-8.94). Mothers aged <20 years are at high risk for spontaneous abortion.